2011
DOI: 10.1186/1471-2474-12-252
|View full text |Cite
|
Sign up to set email alerts
|

Course and prognosis of recovery for chronic non-specific low back pain: design, therapy program and baseline data of a prospective cohort study

Abstract: BackgroundThere has been increasing focus on factors predicting the development of chronic musculoskeletal disorders. For patients already experiencing chronic non-specific low back pain it is also relevant to investigate which prognostic factors predict recovery. We present the design of a cohort study that aims to determine the course and prognostic factors for recovery in patients with chronic non-specific low back pain.Methods/DesignAll participating patients were recruited (Jan 2003-Dec 2008) from the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 69 publications
(62 reference statements)
0
24
1
Order By: Relevance
“…The outcome work-participation is 1 of the 5 outcomes (back pain intensity, disability due to back pain, work-participation, quality of life and patients' perceived recovery) measured in this prospective cohort. For all the outcomes the same 23 prognostic factors were included (7). BMI was changed into a categorical variable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The outcome work-participation is 1 of the 5 outcomes (back pain intensity, disability due to back pain, work-participation, quality of life and patients' perceived recovery) measured in this prospective cohort. For all the outcomes the same 23 prognostic factors were included (7). BMI was changed into a categorical variable.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol was approved by the medical ethics committee of the SJC and all patients provided informed consent. Details of the study design are described elsewhere (7). All patients with CNSLBP were recruited between January 2003 and December 2008 at the SJC.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…6 The symptoms of CLBP, particularly pain, can interfere with the ability to perform basic ADLs such as walking, sitting, standing, sleeping, and lifting. 7,8 Patients with CLBP have a lower level of daily physical activities compared with nonsymptomatic controls. 9 A recent literature review concluded that the effect of CLBP on a patient's ability to perform ADLs can also vary by factors other than symptoms, such as sex, self-efficacy, and fear of movement or reinjury.…”
mentioning
confidence: 98%